Pretty good house : a guide to creating better homes - Kolbert, Dan; Mottram, Emily; Maines, Michael; Briley, Chris (The Taunton Press, 2022)
"Pretty Good House provides a framework and set of guidelines for building or renovating a high-performance home that focus on its inhabitants and the environment--but keeps in mind that few people have pockets deep enough to achieve a "perfect" solution. The essential idea is for homeowners to work within their financial and practical constraints both to meet their own needs and do as much for the planet as possible. A Pretty Good House is : A house that's as small as possible. Simple and durable, but also well designed. Insulated and air-sealed. Above all, it is affordable, healthy, responsible, and resilient."--